Spruce-fir landscape: Upper Gunnison River Basin, Colorado Social-Ecological Climate Resilience Project - Rondeau, R., author; Neely, B., author; Bidwell, M., author; Rangwala, I., author; Yung, L., author; Clifford, K., author; Schulz, T., author; Colorado Natural Heritage Program, publisher (Colorado State University. Libraries, 2017)
Utilizing the climate stories to understand the impacts to social and ecological landscapes, the team worked with stakeholders to develop three overarching landscape scale adaptation strategies for the spruce‐fir landscape. Each of these strategies has a suite of potential actions required to reach a desired future condition. The two primary disturbances of concern that are likely to be exacerbated by climate change in the spruce‐fir forest are wildfire and insect outbreaks; the impacts of greatest concern to this landscape are altered fire regime and altered species composition. The three key strategies developed through this project to address these and other climate impacts are: 1) identify and protect climate refugia sites (persistent areas), 2) maintain or enhance the resilience of the climate refugia sites, and 3) accept, assist, and allow for transformation in non‐climate refugia sites. If adopted by the local community, including land managers and landowners, the framework and strategies resulting from this project can help to reduce the adverse impacts of climate change, allowing for a more sustainable human and natural landscape.
Prepared with: The Gunnison Climate Working Group and Stakeholders in Gunnison, Colorado for: the North Central Climate Science Center, Ft. Collins, Colorado.
April 30, 2017.
Keywords: spruce; fir; climate science; ecological impact; environmental change; natural resource management